Pemicu Tindakan Terorisme di Kabupaten Lamongan - Mohammad Sirojuddin (Universitas Islam Darul Ulum Lamongan, 2019)
One of the problems that continues to emerge in the Indonesian public sphere is religious intolerance, radicalization and terrorism. Religious intolerance, radicalization and terrorism are manifested in the prohibition of religious worship activities, the spread of hatred, religious based violence or the destruction of places of worship. In addition to increasingly diverse forms of intolerance, the area is also expanding. Early studies show that there is a strong geographical link between the growth of religious intolerance and the recruitment of terrorist groups and ISIS. Religious intolerance has occurred in almost all regions of Indonesia, as well as the radicalization of religion and terrorism. The purpose of this research is to provide an adequate and strong explanation related to the nature and causes of intolerance, radicalism and terrorism in Indonesia. This research specifically wants to find out more clearly and in depth about why and how some Indonesians have a tendency to turn into intolerance and radicals, or on the other hand, why and how some others can maintain the values of tolerance.